THE DEVELOPMENT OF A REALISTIC MATHEMATICS APPROACHES TO SOLVE THREE-DIMENSIONAL SHAPES WITH CURVED SURFACES PROBLEMS - Mataheru, Wilmintjie; Huwaa, Novalin C (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2022)
This study aims to develop a validity of learning tools for the curved side space material for grade IX students of SMP in Ambon City in the 2021/2022 academic year using a realistic mathematics approach. The learning device development model used is to modify the 4-D model, which is limited only to the development stage, namely the learning device trial. The data in this study were analyzed quantitatively. The results showed that the learning device that used a realistic mathematical approach in problem-solving the build a curved side spaces problem met the valid criteria at the end of the test